STATUS GIZI DAN LITERASI NUTRISI ORANG TUA SEBAGAI PREDIKTOR KUALITAS HIDUP TERKAIT KESEHATAN PADA ANAK DI DAERAH PEDESAAN - Maria Natalia Indawati; Areta Idarto; Lydia; Natalia Yuwono; Nathania Dwi Kencanawati (CV. Lafadz Jaya, 2026)
Low parental nutrition literacy is a major risk factor contributing to growth disorders in children within rural areas. This study aims to evaluate the effectiveness of nutritional education and growth stimulation interventions in improving parental knowledge in Sajen Village, Mojokerto. The research method employed was a quantitative study with a pre-test and post-test design involving 50 participants. The intervention was conducted through structured counseling supported by educational media, including booklets and flashcards. Analysis results showed a significant increase in the mean knowledge score, where the pre-test score of 15.62 ± 3.25 rose to 19.12 ± 2.77 in the post-test. The mean score difference was 3.5 points, representing a 22.4% increase compared to the baseline. Distributively, 78% of participants experienced an increase in scores, with the highest improvement reaching 13 points. This study concludes that community-based nutritional education interventions are effective in significantly enhancing parental knowledge. These findings support the necessity of implementing similar sustainable educational programs as a preventive measure to improve children's health quality in rural communities.